Agile marketing - Accardi-Petersen, Michelle; SpringerLink (Online service). ([United States] New York Apress, 2011)
Clearly the marketing methods of old will not fulfill all the needs of today's organization. Today, the fast moving opportunities afforded by the internet, websites, social networking and data communication give those in the know a huge advantage over traditional marketers. The goal of this book is to teach you how.
Electronic reproduction.
Keywords: Marketing -- United States; Business enterprises -- Marketing; Electronic books